Abstract 15159: Differential Recovery Between Regional Cerebral Oxygen Saturation and Physiological Parameters in Cardiopulmonary Arrest Patients After Return of Spontaneous Circulation - Tajima, Goro; Shiozaki, Tadahiko; Ogawa, Yoshihito; Hirose, Tomoya; Mori, Nobuto; Ueki, Tomohiro; Izumino, Hiroo; Yamano, Shuhei; Hirao, Tomohito; Inokuma, Takamitsu; Yamashita, Kazunori; Tasaki, Osamu (Circulation, 2015)
ObjectiveWe aimed to clarify the change in rSO2, blood pressure (BP) and arterial oxygen saturation (SpO2) in CPA patients who got return of spontaneous circulation (ROSC).MethodWe measured rSO2 in CPA patients who were transferred to two tertiary emergency medical centers. On arrival, rSO2 sensor was attached to the forehead of patients, and monitored continuously during cardiopulmonary resuscitation. In the patients who got ROSC, we compared change in rSO2 and BP, SpO2, and evaluated the correlation between rSO2 and physiological parameters.ResultThere were 79 CPA patients transferred to the tertiary emergency medical centers, and 38 patients got ROSC(Mean Age 74.8,M:F=25:13). rSO2 increased after ROSC, and showed the significance after 10 minutes after ROSC. Median rSO2 just after ROSC (ROSC 0) was 54.4% (47.2-59.5), and 66.0% (61.8-70.0) in 10 minutes after ROSC (ROSC 10) (Figure, p<0.01 ROSC 0 vs ROSC 10). However, in BP and SpO2, there were no significant difference between in ROSC 0 and ROSC 10. BP rather showed lower tendency in ROSC 10 compared to ROSC 0. BP; 97mmHg (82.0-127) vs 82.0mmHg (67.0-120), SpO2; 86.0% (70.8-95.0) vs 93.0% (76.0-98.3)ConclusionWe clarified that there is a delay in rSO2 recovery compared to BP, SpO2 recovery after ROSC in CPA patients. It might be a therapeutic point to correct the delay in rSO2 recovery.